The moral aspects of lending - Fekete, Orsolya; Tatay, Tibor (Acta Scientiarum Socialium, 2013)
The moral aspects of lending Indebtedness of Hungarian households led to considerable social and economic problems after the 2008 crisis. Many debtors have come to difficult financial situation in Hungary since 2008. The share of non-performing loans have been constantly increasing. As it is raised from time to time, nowadays the question whether terms and conditions set forth in banking contracts conflict moral norms set by the society is one of the key matters to discuss. One may ask whether terms that might be contested from business ethics and social-moral viewpoints be subject to revision under current law or not. How does law interpret ’conflict of public mores’ in a certain period? The paper gives a brief overview of Jewish-Christian roots that feed ethical and moral expectations of the society. The current Hungarian law offers plenty of means to defend loan debtors, but in crisis there are other decisions left unregulated by law requiring ethical consideration which may also influence the relationship of lenders and borrowers.